Neuropathology of Aging in Cats and its Similarities to Human Alzheimer’s Disease - Sordo, Lorena; Martini, Alessandra C.; Houston, E. Fiona; Head, Elizabeth; Gunn-Moore, Danièlle (Frontiers in Aging, 2021)
Elderly cats develop age-related behavioral and neuropathological changes that ultimately lead to cognitive dysfunction syndrome (CDS). These neuropathologies share similarities to those seen in the brains of humans with Alzheimer’s disease (AD), including the extracellular accumulation of -amyloid (A) and intraneuronal deposits of hyperphosphorylated tau, which are considered to be the two major hallmarks of AD. The present study assessed the presence and distribution of A and tau hyperphosphorylation within the cat brain (n=55 cats), and how the distribution of these proteins changes with age and the presence of CDS. For this, immunohistochemistry was performed on seven brain regions from cats of various ages, with and without CDS (n=10 with CDS). Cats accumulate both intracytoplasmic and extracellular deposits of A, as well as intranuclear and intracytoplasmic hyperphosphorylated tau deposits. Large extracellular aggregates of A were found in elderly cats, mainly in the cortical brain areas, with occasional hippocampal aggregates. This may suggest that these aggregates start in cortical areas and later progress to the hippocampus. While A senile plaques in people with AD have a dense core, extracellular A deposits in cats exhibited a diffuse pattern, similar to the early stages of plaque pathogenesis. Intraneuronal A deposits were also observed, occurring predominantly in cortical brain regions of younger cats, while older cats had few to no intraneuronal A deposits, especially when extracellular aggregates were abundant. Intracytoplasmic hyperphosphorylated tau was found within neurones in the brains of elderly cats, particularly in those with CDS. Due to their ultrastructural features, these deposits are considered to be pre-tangles, which are an early stage of the neurofibrillary tangles seen in AD. The largest numbers of pre-tangles are found mainly in the cerebral cortex of elderly cats, whereas lower numbers were found in other regions (i.e., entorhinal cortex and hippocampus). For the first time, intranuclear tau was found in both phosphorylated and non-phosphorylated states within neurons in the cat brain. The highest numbers of intranuclear deposits were found in the cortex of younger cats, and this tended to decrease with age. In contrast, elderly cats with pre-tangles had only occasional or no nuclear labelling.